1998
DOI: 10.1103/physrevlett.80.2169
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Sticking, Scattering, and Transmission ofH4eatoms from SuperfluidH

Abstract: We develop a microscopic theory of the scattering, transmission, and sticking of 4 He atoms impinging on a superfluid 4 He slab at near normal incidence, and inelastic neutron scattering from the slab. The theory includes coupling between different modes and allows for inelastic processes. We find a number of essential aspects that must be observed in a physically meaningful and reliable theory of atom transmission and scattering; all are connected with multiparticle scattering, particularly the possibility of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Among their most recent results are the measurements of the evaporation probability for R + and R − rotons. This is particularly interesting since the calculation of this probability has been a challenge for several groups of theorists [7,25,31,[39][40][41][42][43].…”
Section: Later Experiments and Theoretical Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among their most recent results are the measurements of the evaporation probability for R + and R − rotons. This is particularly interesting since the calculation of this probability has been a challenge for several groups of theorists [7,25,31,[39][40][41][42][43].…”
Section: Later Experiments and Theoretical Developmentsmentioning
confidence: 99%
“…They considered their results as consistent with those of Balibar [14,19] at least in the sense that their observation of roton emission by atom absorption confirms the existence of the reverse process. However, in their calculations of condensation probabilities, Echenique and Pendry [26], Edwards and Fatouros [27], Goodman and Garcia [28], Usagawa [29], Swanson and Edwards [30], and Campbell [31] included the generation of ripplons, which means that, according to them, condensation and evaporation are not purely elastic one-to-one processes.…”
Section: More Experiments In the Seventiesmentioning
confidence: 99%
“…Liquid 4 He is a dynamic, many-body system and incoming particles may scatter into states other than the elastic channel. Recently, Campbell and co-workers 45 have studied the transmission of 4 He atoms through a helium slab and found that inelastic processes dominate the scattering-at around the roton minimum energy, the calculated signal has a sharp dip, showing that, at that energy, inelastic processes take up to about 90% of the energy of the incoming atoms.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…The equation for the quantities of major interest, namely the probabilities of elastic reflection and transmission as well as the probability of inelastic scattering takes the form [2] …”
Section: Target Applicationmentioning
confidence: 99%